Afinal, quantos éramos? Um estudo da mortalidade pretérita na freguesia da gloriosa Sant Anna - Santos, Gracineide Pereira dos (2013)
Search mortality in the glorious St. Anna Parish, hinterland of Rio Grande do Norte in the time frame 1788-1838 is the main objective of this research. Questions that the research aims to answer are: how many were after? Data parish deaths allow us to study mortality in Town? To conduct the research, first appealed to the population maps of the years 1777, 1810, 1811, 1824, 1844, 1853; censuses of 1872 and 1890. As well, the first two books of burials / deaths of the Parish, the first dating from 1788 to 1811 and the second from 1812 to 1838 and a book of baptism 1803-1806. Among the findings it was realized that, for now, the question of knowing, "After all, how many were?" Still cannot be answered, because during the analysis we noticed a high rate of underreporting, demonstrated through a study of the first infant mortality, in which the records we have was very high, which goes against the pre-transitional period, but with the exercise of inverse projection found the opposite, a population that would have a life expectancy higher. Demonstrating the problem of underreporting. Infant deaths occur mainly with the male children in the first months of the year due to infectious causes, and in the early days and weeks, we raised a hypothesis is that these deaths have as a backdrop the poor condition of the mother leading to poor training child, thus leading to his early death